Molecular Variations Linked to the Grouping of β- and α-Globin Genes in Neonatal Patients with Sickle Cell Disease in the State of Pernambuco, Brazil - Bezerra, Marcos André C.; Santos, Magnun N.N.; Araújo, Aderson S.; Gomes, Yara M.; Abath, Frederico G.C.; Bandeira, Flavia M.G.C. (Hemoglobin, 2007)
Various factors have been described as phenotypic modulators of sickle cell disease, such as levels of fetal hemoglobin (Hb F), presence of α-thalassemia (thal), and haplotypes of the β-globin genes. In order to characterize and determine the frequency of the βS and βC mutations and the prevalence of −α3.7-thal, 74 patients with sickle cell disease detected during neonatal screening in the State of Pernambuco, Brazil, were studied. The haplotypes of the β gene and −α3.7-thal were determined using polymerase chain reaction (PCR), and specific restriction endonucleases were used to establish the polymorphic sites of the haplotypes. The results showed the high frequency of the Central African Republic (CAR) or Bantu haplotype in the State of Pernambuco, Brazil. The low frequency of the Benin haplotype recorded in this study, in comparison with other states in northeast Brazil, suggests the diversity of origins of Afro-Brazilians in this region.